Electrochemical behavior of Bi4B2O9 towards lithium-reversible conversion reactions without nanosizing. Issue 4 (5th January 2018) - Strauss, Florian; Rousse, Gwenaëlle; Batuk, Dmitry; Tang, Mingxue; Salager, Elodie; Dražić, Goran; Dominko, Robert; Tarascon, Jean-Marie
Abstract : Galvanostatic charge–discharge curves for a Bi4 B2 O9 /C macrocomposite, highlighting the small voltage hysteresis for the conversion reaction around 300 mV. Abstract : Conversion type materials, in particular metal fluorides, have emerged as attractive candidates for positive electrodes in next generation Li-ion batteries (LIBs). However, their practical use is being hindered by issues related to reversibility and large polarization. To minimize these issues, a few approaches enlisting the anionic network have been considered. We herein report the electrochemical properties of bismuth oxyborate Bi4 B2 O9 and show that this compound reacts with lithium via a conversion reaction leading to a sustained capacity of 140 mA h g −1 when cycled between 1.7 and 3.5 V vs. Li + /Li 0 while having a surprisingly small polarization (∼300 mV) in the presence of solely 5% in weight of a carbon additive. These observations are rationalized in terms of charge transfer kinetics via complementary XRD, HRTEM and NMR measurements. This finding demonstrates that borate based conversion type materials display rapid charge transfer with limited carbon additives, hence offering a new strategy to improve their overall cycling efficiency.